Little disasters : [large type] a novel - Vaughan, Sarah, 1972- (Thorndike Press large print basic, 2020)
"Liz Trenchard is an experienced pediatrician with a duty to protect all children admitted to ber busy emergency room. She has been friends with Jess for a decade and view the tay-at-home mother-of-three as a woman with boundless reserves of patience, energy, and love. Then one moment changes everything. When Jess turns up in the ER one night with her baby girl and a story that doesn't quite add up, Liz is forced to question everything she thought she knew about her friend and about herself"--Page 4 of cover.